Insecticidal Activity, Toxicity, Resistance and Metabolism of Pyrethroids: a Review - Ashutosh Singh; Abhishek Singh; Preeti Singh; Archana Chakravarty; Akhilesh Singh; Priti Singh; Mahendra Kumar Mishra; Vivek Singh; Atul Kumar Srivastava; Himanshu Aggarwal; Suresh Sagadevan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Pyrethroids are synthetic or man-made versions of natural pyrethrins discovered in the flowers of a plant species of the Compositae family called